Determination of Minimum Inhibitory Concentration (MIC) of Tigecycline against Salmonella typhi (The Journal of Ad-din Women's Medical College, 2023)
Introduction: Typhoid fever, caused by S. Typhi, is prevalent in developing countries, particularly the Indian subcontinent. Salmonella infections can cause enteric fever, gastroenteritis, septicemia, and non-typhoidal Salmonellae (NTS) infections, especially in immunocompromised patients.Objective: To determine the Minimum Inhibitory Concentration (MIC) of Tigecycline against Salmonella Typhi.Methodology: This interventional study conducted at Department of Pharmacology & Therapeutics in collaboration with Department of Microbiology at Ad-din Sakina Women’s Medical College, Jashore during March 2023 to April 2023.MIC of Tigecycline was determined by Broth Dilution Technique against standard strain of Salmonella typhi ATCC 24683.Result: The MIC of Tigecycline against Salmonella typhi was 2.0 μg/ml.Conclusion: Tigecycline is a potential therapeutic agent for Salmonella typhi infection, and should be restricted on the basis of blood culture and in MDR and XDR cases of typhoid fever only.The Journal of Ad-din Women's Medical College; Vol. 11 (2), July 2023; p 15-19